2006
DOI: 10.1161/circulationaha.106.622076
|View full text |Cite
|
Sign up to set email alerts
|

Transvenous Pacing Leads and Systemic Thromboemboli in Patients With Intracardiac Shunts

Abstract: Background— The risk of systemic thromboemboli associated with transvenous leads in the presence of an intracardiac shunt is currently unknown. Methods and Results— To define this risk, we conducted a multicenter, retrospective cohort study of 202 patients with intracardiac shunts: Sixty-four had transvenous leads (group 1), 56 had epicardial leads (group 2), and 82 had right-to-left shunts but no pacemaker or im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
117
0
16

Year Published

2006
2006
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 273 publications
(133 citation statements)
references
References 40 publications
0
117
0
16
Order By: Relevance
“…Transvenous implantation often cannot be performed in children due to patient size, lack of vascular access and increased risk of embolic phenomena due to intracardiac shunts. 5,31 Children with ICDs have high rates both of lead failure and vascular occlusion, and also have long life expectancy compared to adult patients, resulting in the anticipated need for repeated lead extraction and reimplantation with their attendant risks. 1,6 There is now also growing interest in the development of extracardiac, subcutaneous ICDs for the adult population with normal cardiac anatomy, with the goal of simplifying ICD implantation, avoiding lead related complications, and/or addressing vascular access problems or other contraindications to transvenous implant.…”
Section: Discussionmentioning
confidence: 99%
“…Transvenous implantation often cannot be performed in children due to patient size, lack of vascular access and increased risk of embolic phenomena due to intracardiac shunts. 5,31 Children with ICDs have high rates both of lead failure and vascular occlusion, and also have long life expectancy compared to adult patients, resulting in the anticipated need for repeated lead extraction and reimplantation with their attendant risks. 1,6 There is now also growing interest in the development of extracardiac, subcutaneous ICDs for the adult population with normal cardiac anatomy, with the goal of simplifying ICD implantation, avoiding lead related complications, and/or addressing vascular access problems or other contraindications to transvenous implant.…”
Section: Discussionmentioning
confidence: 99%
“…Hemodynamic evaluation demonstrated a brief shunt reversal, creating a paradoxical right-to-left shunt through the defect. Khairy et al 532 demonstrated that transvenous leads were a multifactorial independent risk for emboli regardless of shunt direction. In addition, some patients had embolic complications despite aspirin or warfarin with a therapeutic INR.…”
Section: Pacemakers and Internal Cardiac Defibrillatorsmentioning
confidence: 99%
“…14 The presence of an intracardiac shunt, including baffle leak, increases the risk of paradoxical thromboembolic events arising from transvenous leads >2-fold. 15 Although there are few data, anticoagulation therapy should be considered in patients with intracardiac shunts receiving transvenous leads.…”
Section: Discussion and Literature Reviewmentioning
confidence: 99%